Interaction Between the Complement System and Infectious Agents – A Potential Mechanistic Link to Neurodegeneration and Dementia - Shinjyo, Noriko; Kagaya, Wataru; Pekna, Marcela (Frontiers in Cellular Neuroscience, 2021)
As part of the innate immune system, complement plays a critical role in the elimination of pathogens and mobilization of cellular immune responses. In the central nervous system (CNS), many complement proteins are locally produced and regulate nervous system development and physiological processes such as neural plasticity. However, aberrant complement activation has been implicated in neurodegeneration, including Alzheimer’s disease. There is a growing list of pathogens that have been shown to interact with the complement system in the brain but the short- and long-term consequences of infection-induced complement activation for neuronal functioning are largely elusive. Available evidence suggests that the infection-induced complement activation could be protective or harmful, depending on the context. Here we summarize how various infectious agents, including bacteria (e.g., Streptococcus spp.), viruses (e.g., HIV and measles virus), fungi (e.g., Candida spp.), parasites (e.g., Toxoplasma gondii and Plasmodium spp.), and prion proteins activate and manipulate the complement system in the CNS. We also discuss the potential mechanisms by which the interaction between the infectious agents and the complement system can play a role in neurodegeneration and dementia.